1996
DOI: 10.1093/humrep/11.suppl_2.51
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial angiogenic response in Norplant users

Abstract: The levonorgestrel-releasing subdermal contraceptive implant Norplant is well accepted among Indonesian users, despite the problems with irregular and prolonged menstrual bleeding. Bleeding can be the major reason for women discontinuing their use of Norplant. The causes of endometrial bleeding may include disturbances in endometrial regeneration and angiogenesis. The aim of this study was to investigate endometrial angiogenic activity in Norplant users and to compare it to that in the normal menstrual cycle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The local mechanisms that cause endometrial bleeding are still unclear. Following 3-12 months of Norplant use, the endometrium becomes very thin and the angiogenic response is decreased (Subakir et al, 1996). The spiral arteries are small and underdeveloped with increased dilatation of the veins and breaks in the endothelial lining (Hourihan et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The local mechanisms that cause endometrial bleeding are still unclear. Following 3-12 months of Norplant use, the endometrium becomes very thin and the angiogenic response is decreased (Subakir et al, 1996). The spiral arteries are small and underdeveloped with increased dilatation of the veins and breaks in the endothelial lining (Hourihan et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Following exposure to progestin-only contraceptives, BTB tends to be prolonged or irregular, suggesting that normal endometrial repair mechanisms may be dysfunctional. In a previous study we have shown that decreased endometrial angiogenic response in Norplant users was not correlated with plasma concentrations of oestradiol, progesterone, sex hormone binding globulin (SHBG) or LNG (Subakir et al, 1996). Vitamin E is the major physiological lipidsoluble chain-breaking antioxidant, preventing peroxidation, and also modulates the metabolism of arachidonic acid (Packer and Lanvick, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a previous study by Subakir et al, has shown that tissue from patients with menorrhagia may have elevated angiogenic potential. 19,21 Kooy et al in their study found that there was no significant difference in cellular proliferation in the stroma of endometrium from controls, patients with menorrhagia. 19 This indicated that the increase in endothelial cell proliferation in endometrium from patients with menorrhagia was specific and not the result of a general increase of cellular proliferation in the endometrium.…”
Section: Discussionmentioning
confidence: 92%
“…22 Rogers have shown repeatedly that levels of endothelial cells proliferation within human endometrium did not show any consistent pattern across the different stages of the menstrual cycle. 5,[19][20][21][22] Gargett et al found a highly significant correlation between the percentage of VEGF expressing vessels and vessels containing proliferating endothelial cells. 23 The percentage of proliferating vessels was higher in proliferative compared to secretory endometrium, but this was only statistically significant in the basalis layer.…”
Section: Discussionmentioning
confidence: 99%
“…Rashidi et al demonstrated that P4 attenuates EC proliferation induced by gonadotropins, leading to an inhibitory effect on endometrial angiogenesis [ 121 ], and a consistent pattern has been found in ectopic endometrial lesions [ 68 ]. Synthetic progestins have a similar influence, and several studies have revealed that the levonorgestrel-releasing subdermal contraceptive has an anti-angiogenic effect, and that it significantly inhibits the proliferation rate of endometrial ECs, which results in reduced endometrial angiogenic activity [ 122 , 123 ]. Further, a sustained peak expression of cyclin E and A has been observed in this process, resulting in arresting of the EC cycle in G1 [ 124 ].…”
Section: Progestogen-mediated Physiological Neovascularizationmentioning
confidence: 99%